Trying again (and again): Weight cycling and depressive symptoms in U.S. adults. - Diane M Quinn; Rebecca M Puhl; Mora A Reinka (PLoS ONE, 2020)
As the prevalence of overweight and obesity have risen over the past few decades, so have weight control attempts. Research has shown, however, that intentional weight loss results are often short-lived, with people regaining the weight over time. This can lead to weight cycling-losing and gaining weight repeatedly. Previous research, mostly done over two decades ago, concluded there was no relationship between weight cycling and psychological health. The goal of the current paper was to re-examine the relationship between weight cycling and depressive symptoms in a national sample of American adults (N = 2702; 50.7% female; mean age = 44.8 years). If, as hypothesized, there is a relationship between more frequent weight cycling and depressive symptoms, then internalized weight stigma will be examined as a potential mediator of the relationship. Results of a cross-sectional survey showed that 74.6% of adults report they have intentionally tried to lose weight. Amongst those who have tried to lose to weight, the average number of weight cycles over the lifetime was 7.82 cycles. Simultaneous regression showed that greater weight cycling was related to greater reported depressive symptoms (β = .15, p < .001), controlling for age, gender, education, income, and body mass index. Internalized weight stigma was a partial mediator of this relationship. Discussion focuses on the potential implications for weight cycling and mental health.